Computer Science Illuminated / Fifth Edition - Dale Nell; Lewis John (Jones And Bartlett Learning, 2013)
An engaging Breadth-first Overview of Computer Science Principles and a solid foundation for those continuing their study in this dynamic and exciting discipline. Laying the Groundwork, The Information Layer, The Hardware Layer, The Programming Layer, The Operating Systems Layer, The Applications Layer, The Communications Layer, In Conclusion.